Epidemiological aspects of Hand, Foot and Mouth Disease in Sarawak, Malaysia - Mohammad Sham, Noraishah (2017)
Hand, Foot and Mouth Disease (HFMD) is a contagious disease in human population especially infants and children. In Sarawak, Malaysia, the disease is endemic. Since the first outbreak in 1997, Sarawak remains as the state with the highest number of HFMD notified cases among other states in Malaysia. In Malaysia, there have been many studies related to HFMD that investigates the clinical aspects of the disease. In this study, we aim to study the epidemiological aspects of HFMD in Sarawak, Malaysia and to provide beneficial information based on the analysis of the data in order to reduce the spread of HFMD in Malaysia. In order to achieve the objective of this study, we observe the effect of non-random mixing patterns of HFMD notified cases in Sarawak, Malaysia; obtain appropriate time series model and forecast future HFMD outbreaks in Sarawak, Malaysia; observe the impact of climatic factors on HFMD in Sarawak, Malaysia; analyze spatial and temporal patterns of HFMD in Sarawak, Malaysia and provide recommendations for future HFMD surveillance and control programme in Sarawak, Malaysia. In order for us to really understand the insights of HFMD, we characterized the disease by analyzing 71,512 HFMD notifications from week 1, 2006 to week 52, 2013 for Sarawak, Malaysia. The dataset was obtained from Infectious Disease Control Section (IDSC), Sarawak State Health Department (SSHD). Analysis of HFMD during the study period showed that the disease outbreak in 2006 was the highest with 14,875 notified cases. A three-year (2011-2013) daily data of 24,879 notifications were used to study the effects of age factors in a non-random mixing pattern. As a result, 76.95 percentage (18,427) of children below the age of five were predominant to HFMD in Sarawak. It is also shown that the ratio of male to female is slightly higher for this age group. HFMD can spread through close personal contact, the air (through coughing or sneezing), contact with feces or contaminated objects and surfaces. Few countries claimed that climate played a role to the disease transmission. A time series model is constructed with and without the climate factors such as temperature and rainfall to see the effect of climatic factors on the spread of HFMD. The feasibility and practicality of modelling and forecasting HFMD trends was demonstrated. ARMA (Autoregressive Moving Average) and ARMAX (Auto Regressive Moving Average with exogenous variables) models were generated using HFMD notification data and climate variables from 2006 to 2012. The forecast result was then compared to the actual HFMD notification data in 2013. It is found that ARMA(1,4) model is able to give good prediction and forecast at 94 percent of the notified cases fall within the 90 percent forecast interval based on historical data. We analyze temporal and spatial patterns of the disease in Sarawak using Geographical Information System (GIS). We evaluated the potential of clustering of HFMD notified cases by divisions in Sarawak using two approaches; choropleth mapping and spatial interpolation. We also analyzed the effects of locality which can demonstrate the high or low risk of HFMD notified cases between the rural and urban divisions. The findings indicate that during the outbreak year (2012), spatial autocorrelation exist between the divisions. However, visually HFMD notified cases can be seen to be clustered covering neighbouring divisions in the center of the state also in year 2009. Moreover, high risk was found in urban divisions of Sarawak during the outbreak year. This study has provided valuable information to the knowledge of HFMD epidemiology, trends and patterns in Sarawak, Malaysia which would help in containing the disease. In addition, throughout this study, few new areas of research were identified and recommendations have been developed in order to enhance HFMD surveillance, prevention and control in Malaysia.